STATISTICAL ANALYSIS OF PATIENTS WITH DIABETES 2 DISEASE (in the example of the city of Nukus in 2025) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
The incidence of diabetes mellitus (DM) is rapidly increasing in all countries of the world due to the prevalence of obesity, sedentary lifestyle and poor diet. According to the International Diabetes Federation (IDF), in 2021, 735 million patients with diabetes are registered in the world; by 2040, the projected number of patients will increase to 1042 million. It should be noted that the actual prevalence of type 2 diabetes in most countries of the world is 2 –3 times higher than the registered one [1]. The negative impact of decompensated diabetes mellitus on a woman’s reproductive system is known.